Application of serum natalizumab levels during plasma exchange in MS patients with progressive multifocal leukoencephalopathy. (April 2015) - Vennegoor, A; Rispens, T; Van Oosten, BW; Wattjes, MP; Wondergem, MJ; Teunissen, CE; Van der Kleij, D; Uitdehaag, BMJ; Polman, CH; Killestein, J
Progressive multifocal leukoencephalopathy (PML) is a severe complication of natalizumab treatment. Restoring immune function by plasmapheresis/immunoadsorption (PLEX/IA) is important for the outcome of PML. We report on four multiple sclerosis (MS) patients whom developed PML during natalizumab treatment, in whom we measured serum natalizumab concentrations before and during PLEX. Depending on the serum natalizumab concentration at the time of PML diagnosis, the number of PLEX treatments necessary to reach subtherapeutic serum natalizumab concentrations is variable. Measuring serum natalizumab concentrations before and during PLEX is helpful to determine the optimum number of PLEX treatments in individual MS patients with PML.